Analisis Biaya Transportasi dari Lingkungan Pemukiman Terhadap Pusat Kota Manado - Jufry Rompas (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
To support the smooth activities of the people who live in housing, it is necessary to have good transportation accessibility in the residential area to the city center. This study aims to determine the level of transportation accessibility in the new housing environment in Manado City, especially in the northern part of the city center. In this study, the primary data for analysis was obtained using a questionnaire, and the sample was selected using a simple random sample method. Secondary data obtained from the relevant agencies. The method used is simple regression analysis and the Dial model. With both methods, the level of accessibility is measured based on the parameters of distance, cost and travel time. The results of the simple regression analysis show high accessibility, seen from the parameters of distance, cost and travel time, while the Dial model analysis, the probability of choosing a route is only shown by the distance parameter, because the. Level of accessibility that occurs is more influenced by the characteristics offered on each route.